2013
DOI: 10.4304/tpls.3.9.1674-1679
|View full text |Cite
|
Sign up to set email alerts
|

Gender Representation in Children's EFL Textbooks

Abstract: Abstract-The differences in the speech and behavior of adult males and females may be a consequence of their sexist education in childhood; experimental research suggests that the development of children's gender identity is strongly affected by their reading materials and extensive research on these materials have revealed that gender bias and gender stereotypes are prevalent. The present study examines the representation of gender in conversations, illustrations and graphic design of the cover in nine packag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 12 publications
2
15
0
1
Order By: Relevance
“…In terms of the Inclusion/Exclusion dichotomy, these series show a more promising picture compared to the older series where females were mostly marginalized. This finding is in line with Parham (2013) The descriptive data from the questionnaire yielded different response patterns across male and female teachers. The interpretation from the descriptive part, as it concerns research question 3, hinges upon contextual factors.…”
Section: Conclusion and Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…In terms of the Inclusion/Exclusion dichotomy, these series show a more promising picture compared to the older series where females were mostly marginalized. This finding is in line with Parham (2013) The descriptive data from the questionnaire yielded different response patterns across male and female teachers. The interpretation from the descriptive part, as it concerns research question 3, hinges upon contextual factors.…”
Section: Conclusion and Discussionsupporting
confidence: 77%
“…Parham (2013) investigated gender representation in 'English Time' series. She could show that there were no significant differences between male and female characters in the conversations regarding the frequency of participation in conversations, number of turns, length of turns, and visibility.…”
Section: Introductionmentioning
confidence: 99%
“…Investigaciones sobre el sexismo en los libros de texto en diversas materias evidencian la menor frecuencia de aparición de personajes femeninos frente a personajes masculinos, y por lo tanto, la desigualdad entre géneros (Blanco, 2003;Gallardo, 2008;López-Navajas, 2014;Parham, 2013;Terrón & Cobano-Delgado, 2009).…”
Section: Representación Del Género Y La Cultura Corporal En Los Librounclassified
“…Males were representative of sports and science-related fields while females were consigned to fashion and hospitality. Within children's textbooks used in several Iranian language learning centers, Parham (2013) found that while female figures initiate conversations more frequently than males, they are less represented compared to their male counterparts. This extends up to secondary level in Iran according to an earlier work by Amini and Birjandi (2012).…”
Section: Effects Of Gender Stereotyping On Childrenmentioning
confidence: 99%